PREDNISOLONE VERSUS COMBINATION OF PREDNISOLONE AND IVIG IN TREATMENT OF ACUTE IDIOPATHIC THROMBOCYTOPENIA AMONG CHILDREN - Salim, Siamand Yahya (Journal of Sulaimani Medical College, 2024)
Background Immune thrombocytopenia (ITP) is a medical situation appearing from animmunological reaction, resulting in a decreased platelet count and improved susceptibility to bleeding. Intravenous immunoglobulin (IVIG) in conjunction with corticosteroids, such as prednisolone, is often used as the first medicine practice for children. Nevertheless, there needs to be more information corresponding to the effectiveness of hybrid treatment to corticosteroids alone. Objectives In this study we aim to compare the outcomes of treating patients with prednisoloneas a sole treatment with the combination of prednisolone and IVIG in treating acute immune thrombocytopenic purpura in children. Patients and Methods In this randomized controlled experiment, 42 pediatric patients interpreted with immune thrombocytopenic purpura (ITP) were comprised. These children were unsystematically allocated to two groups: one group got intravenous immunoglobulin (IVIG) in combination with prednisolone (n=21), while the other group accepted prednisolone alone (n=21). Platelet counts were measured at baseline, day 3, and week 2. Results The study’s results demonstrate that the average baseline platelet count was 17.52±4.59 x 109/L, and no notable difference was seen between the groups. On the third day of the study, the hybrid group displayed a statistically meaningful increase in platelet recovery (113.71±26.3 x 109/L) as compared to the group receiving prednisolone alone (80.90±18.09 x 109/L, p<0.001). In the second week, the group acquiring the combined treatment had significantly more significant increases in platelet counts (207.71±45.26 x 109/L) compared to those receiving prednisolone alone (121.62±26.33 x 109/L, p<0.001). Conclusion the management of a combination of intravenous immunoglobulin (IVIG) and prednisolone resulted in a more immediate and considerable elevation in platelet levels as compared to the use of prednisolone alone as a monotherapy in pediatric patients recently analyzed with immune thrombocytopenic purpura (ITP). The results of this study provided proof in favor of the use of IVIG in combination with steroids as a more compelling first treatment option for reducing the risks associated with bleeding. The demographic characteristics and treatment results are consistent with previous empirical discoveries.
Keywords: Immune thrombocytopenia; intravenous immunoglobulin; pediatrics; prednisolone